Never let me go - Ishiguro, Kazuo, 1954- (New York : Vintage International, 2006)
From the Booker Prize-winning author of The Remains of the Day and When We Were Orphans, comes an unforgettable edge-of-your-seat mystery that is at once heartbreakingly tender and morally courageous about what it means to be human. Hailsham seems like a pleasant English boarding school, far from the influences of the city. Its students are well tended and supported, trained in art and literature, and become just the sort of people the world wants them to be. But, curiously, they are taught nothing of the outside world and are allowed little contact with it. Within the grounds of Hailsham, Kathy grows from schoolgirl to young woman, but it's only when she and her friends Ruth and Tommy leave the safe grounds of the school (as they always knew they would) that they realize the full truth of what Hailsham is.
Hailsham seems like a pleasant English boarding school, far from the influences of the city. Its students are well tended and supported, trained in art and literature, and become just the sort of people the world wants them to be. But, curiously, they are taught nothing of the outside world and are allowed little contact with it. Within the grounds of Hailsham, Kathy grows from schoolgirl to young woman, but it's only when she and her friends Ruth and Tommy leave the safe grounds of the school (as they always knew they would) that they realize the full truth of what Hailsham is.
First Vintage International edition, March 2006.
AAL
Keywords: Women -- Fiction; Cloning -- Fiction; Organ donors -- Fiction; Donation of organs, tissues, etc. -- Fiction; Science fiction; Cloning; Donation of organs, tissues, etc; Organ donors; Science fiction; Women; England -- Fiction; England